Regulation of the Financial System in the Republic of Congo - Issie, Franchel Mbon (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2023)
After the 2008 subprime crisis, financial institutions in the Congo (Brazzaville) underwent a series of significant adjustments and reforms in line with their regulatory traditions of systemically important financial institutions, the evolution of the regulatory system, and the country's financial development needs. This paper needs to analyze and study financial regulation in the Republic of Congo. This paper mainly analyzes the current situation of the financial regulatory system of the Republic of the Congo (Brazzaville), finds the problems in the financial regulatory system, collects accessible financial data and financial indicators, and constructs the financial regulatory system of the Republic of the Congo (Brazzaville) with principal component analysis. This paper uses the GARCH-CoVaR model to assess the contribution of banks' systemic risk in Congo Brazzaville. Then, it constructs a risk assessment system for Congo based on the indicator method. The results show that banks' systemic risk is not limited to the systemic risk of individual banks. The systemic risk of banks in the Republic of Congo mainly originates from six major banks: the Central Bank of the State of Congo, the Bank of Congo, the Bank of Commerce and Credit of Congo, the Savings Bank of Congo, the Central Bank for the Development of Central African States, the Central Bank of Africa, and the Central Bank of Africa.